Dynamic Behavior of a Stochastic Tungiasis Model for Public Health Education - Lili Kong; Luping Li; Shugui Kang; Youjun Liu; Wenying Feng (Discrete Dynamics in Nature and Society)
In this paper, we study the dynamic behavior of a stochastic tungiasis model for public health education. First, the existence and uniqueness of global positive solution of stochastic models are proved. Secondly, by constructing Lyapunov function and using Ito^ formula, sufficient conditions for disease extinction and persistence in the stochastic model are proved. Thirdly, under the condition of disease persistence, the existence and uniqueness of an ergodic stationary distribution of the model is obtained. Finally, the importance of public health education in preventing the spread of tungiasis is illustrated through the combination of theoretical results and numerical simulation.